Typical groundwater contamination in the vicinity of industrial brownfields and basic methods of their treatment - Solcova, Olga; Krystynik, Pavel; Dytrych, Pavel; Bumba, Jakub; Kastanek, Frantisek (Ecotoxicology and environmental safety, 2022)
The article deals with simple methods of decontamination of groundwater from the vicinity of brownfields contaminated with organic and inorganic substances. In the literature, thousands of articles on this issue at various sophisticated levels of knowledge can be found. The articles are mostly suitable as an extension of scientific knowledge; however, regarding potential costs and respectively scale-up problems, the applications are limited. It turns out that the vast majority of contaminated water can be effectively decontaminated by simple methods, in a coagulation-sedimentation sequence → simple oxidation and reduction methods for separated water (Fenton reaction, photocatalysis, ozonation, reductive dehalogenation with zero metals) → adsorption of remaining pollutants on simple sorbents, eg on biochar → (possibly bioremediation or advanced physical methods such as membrane filtration) → final purification on activated carbon. Due to the usually limited volume loads of soils with pollutants in the vicinity of brownfields, it is not economically advantageous to build demanding decontamination units for water purification. Usually, the simplest solution is the system to pump-and-treat around the source of contamination, with the main emphasis on highly effective removal of pollutants from water that returns underground. Groundwater was taken from boreholes leading to the saturated zone in the vicinity of several selected industrial brownfields. The solutions are shown on individual typical cases.
Keywords: Water Pollutants, Chemical; Brownfield remediation; podzemní voda; Groundwater; Zerovalent nano-iron; Adsorption; Water Purification; adsorpce; Groundwater treatment; Photocatalysis; čištění vody; Biodegradation, Environmental; biodegradace; chemické látky znečišťující vodu; Electrocoagulation